The Namibian War of Independence 1966 - 1989 ; diplomatic, economic and military campaigns - Dale, Richard 1932- (McFarland, 2014)
"This book describes the diplomatic, economic and military campaigns of the Namibian and South African belligerents and draws a comparison with several other decolonization wars. Using data from parliamentary debates, the aftermath of the Namibian war is examined in terms of the diplomatic, economic and military changes in the newly independent nation"--Provided by publisher
Keywords: Geschichte 1946-1990; Decolonization / Namibia; Geschichte; Politik; Unabhängigkeitsbewegung; Entkolonialisierung; Namibia / History / 1946-1990; Namibia / History / Autonomy and independence movements; Namibia / Politics and government / 1946-1990; Namibia